Ethical conflicts in nursing care in the prison context - P González-Gálvez; M Sánchez-Roig; A Coll Cámara; O Canet Vélez; J Roca Llobet (Sociedad Española de Sanidad Penitenciaria, 2021)
ABSTRACT Objective The general objective of the study is to gather the corresponding evidence with the ethical conflicts that may affect penitentiary nurses. Methods The methodology used consists methodology used consists in a systematic review of narrative analysis in the mayor data-bases by means of an applied search strategy and critical appraisal skills programme español (CASPe). Results A total of 167 studies published between 1998 and 2017 were identified, of which 60 met the inclusion criteria. Conclusion The main conclusion is the need for research on the ethical problems related to the treatment of prisoners and on the search for the benefits of the inmates. In addition to the need for a training in ethics for the prison professionals, the identification of the real health-care needs of the prison population, and the collaboration between the prison assistance and the health system.